2020
DOI: 10.3390/mi11040341
|View full text |Cite
|
Sign up to set email alerts
|

Memristive Non-Volatile Memory Based on Graphene Materials

Abstract: Resistive random access memory (RRAM), which is considered as one of the most promising next-generation non-volatile memory (NVM) devices and a representative of memristor technologies, demonstrated great potential in acting as an artificial synapse in the industry of neuromorphic systems and artificial intelligence (AI), due its advantages such as fast operation speed, low power consumption, and high device density. Graphene and related materials (GRMs), especially graphene oxide (GO), acting as active materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 189 publications
(317 reference statements)
0
50
0
1
Order By: Relevance
“…This 9-nmthickness device exhibited excellent repeatable RS cycles with number of endurance pulses over 10 5 and retention time longer than 3 × 10 4 s. In addition, some RRAM devices with noble metal as both TE and BE also demonstrated bipolar switching performance, such as Pt/sputtering-deposited Cr2O3/Pt reported by Chen et al [132], Pt/sputtering-deposited TaOx/Pt reported by Huang et al [133], Pt/Ni/ECD (electrochemical deposition)-fabricated CuOx/Ni/Pt, and Pt/sputtering-deposited SiO2/Pt reported by Park et al [134]. Apart from elementary substance metals mentioned, carbon-based materials such as graphene and carbon nanotubes [48,62,131,135], conductive oxides such as ITO (indium tin oxide) [131], and complex nitrides such as TiN and TaN [20,85] are also charming as selection of RRAM electrodes. ITO electrode has been widely utilized in electronic devices as well as RRAM cells due to its excellent electrical conductivity, high light transmittance and high hardness [48].…”
Section: Thin Film Materials Of Electrodementioning
confidence: 97%
See 3 more Smart Citations
“…This 9-nmthickness device exhibited excellent repeatable RS cycles with number of endurance pulses over 10 5 and retention time longer than 3 × 10 4 s. In addition, some RRAM devices with noble metal as both TE and BE also demonstrated bipolar switching performance, such as Pt/sputtering-deposited Cr2O3/Pt reported by Chen et al [132], Pt/sputtering-deposited TaOx/Pt reported by Huang et al [133], Pt/Ni/ECD (electrochemical deposition)-fabricated CuOx/Ni/Pt, and Pt/sputtering-deposited SiO2/Pt reported by Park et al [134]. Apart from elementary substance metals mentioned, carbon-based materials such as graphene and carbon nanotubes [48,62,131,135], conductive oxides such as ITO (indium tin oxide) [131], and complex nitrides such as TiN and TaN [20,85] are also charming as selection of RRAM electrodes. ITO electrode has been widely utilized in electronic devices as well as RRAM cells due to its excellent electrical conductivity, high light transmittance and high hardness [48].…”
Section: Thin Film Materials Of Electrodementioning
confidence: 97%
“…Before we present an investigation of materials application, it is necessary to provide brief induction of figures of merit (FoMs), which are mainly used to assess the performance of RRAM devices, including operation speed, power consumption, reliability, scalability, and cost [62]. Operation speed is defined by random-access time and effective time of write & erase (w & e) speed of a single RRAM cell; power consumption is affected by static and dynamic power consumption; reliability consists of endurance; retention properties are used to determine whether an RRAM device is reliable; scalability of an RRAM device determines whether RRAM devices can be developed in line with current trends of increasing device density; and the cost directly has an impact on marketization or mass-production of the proposed devices [62]. Apart from the main FoMs presented above, some other specific characteristics of FoMs such as SET/RESET voltage, ON/OFF switching ratio, distribution of operation voltage, and resistance cannot be neglected accordingly.…”
Section: Thin Film Materials Of Rram Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these electronic devices, resistive random access memory (RRAM) of non-volatile memory (NVM) has attracted a tremendous amount of attention due to its nanoJoule-level power consumption, picosecond-level read & write speed and ~year-level service life [1,4]. For now, it has been proved that oxide materials, including metal oxide (MO) (AlOx, HfOx and NiO) and nonmetal oxides (graphene oxide (GO) and phosphorus oxide (POx)), could demonstrate stable resistive switching (RS) performance in RRAM devices [3,[5][6][7]. However, most oxide RS layers were deposited by traditional fabrication methods like atomic layer deposition (ALD), sputtering and chemical vapor deposition (CVD).…”
Section: Introductionmentioning
confidence: 99%